2014
DOI: 10.1002/asia.201402828
|View full text |Cite
|
Sign up to set email alerts
|

Coordination Chemistry of Highly Hemilabile Bidentate Sulfoxide N‐Heterocyclic Carbenes with Palladium(II)

Abstract: Imidazolium salts, [RS(O)-CH2 (C3 H3 N2 )Mes]Cl (R=Me (L1a), Ph (L1b)); Mes=mesityl), make convenient carbene precursors. Palladation of L1a affords the monodentate dinuclear complex, [(PdCl2 {MeS(O)CH2 (C3 H2 N2 )Mes})2 ] (2a), which is converted into trans-[PdCl2 (NHC)2] (trans-4a; N-heterocyclic carbene) with two rotamers in anti and syn configurations. Complex trans-4a can isomerize into cis-4a(anti) at reflux in acetonitrile. Abstraction of chlorides from 4a or 4b leads to the formation of a new dication:… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
8
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 10 publications
(8 citation statements)
references
References 84 publications
0
8
0
Order By: Relevance
“…The nature of the isomers can be better elucidated through 13 C NMR spectrum (Figure S9). It suggests the presence of the two rotamers trans–syn and trans–anti as frequently observed for nickel(II) and palladium(II) complexes of two unsymmetrical NHC ligands . As a matter of fact, only one carbenic carbon signal at chemical shift typical of trans ‐bis(NHCs)PtX 2 complexes is present ( δ =167.3 ppm) .…”
Section: Figurementioning
confidence: 53%
See 1 more Smart Citation
“…The nature of the isomers can be better elucidated through 13 C NMR spectrum (Figure S9). It suggests the presence of the two rotamers trans–syn and trans–anti as frequently observed for nickel(II) and palladium(II) complexes of two unsymmetrical NHC ligands . As a matter of fact, only one carbenic carbon signal at chemical shift typical of trans ‐bis(NHCs)PtX 2 complexes is present ( δ =167.3 ppm) .…”
Section: Figurementioning
confidence: 53%
“…It suggestst he presence of the two rotamers trans-syn and trans-anti as frequently observed forn ickel(II) and palladium(II) complexes of two unsymmetrical NHC ligands. [49][50][51] As am atter of fact, only one carbenic carbon signal at chemical shift typical of trans-bis(NHCs)PtX 2 complexes is present( d = 167.3 ppm). [48] The formation of the cis isomer can therefore be excluded, as it would have given ac arbenic carbon signal at significantly upfield shiftedc hemical shift as reported for similar compounds (d % 132-150 ppm).…”
mentioning
confidence: 97%
“…Since the recent review published by Fliedel and Braunstein in 2014, 127 very few S-functionalized NHC ligands have been reported. 208,209 An interesting example was described by Liu and Chen and co-workers, 209 who prepared a series of palladium(II) complexes with bidentate sulfoxide-NHC ligands Albrecht and co-workers 153 described in 2014 the preparation of the pincer type NHC-carboxylate complex 121. The coordination and decoordination of the carboxylate arm of the ligand is triggered by addition of a base or acid, respectively.…”
Section: Hemilabile and Conformationally Labile N-heterocyclic Carben...mentioning
confidence: 99%
“…Since the recent review published by Fliedel and Braunstein in 2014, very few S-functionalized NHC ligands have been reported. , An interesting example was described by Liu and Chen and co-workers, who prepared a series of palladium­(II) complexes with bidentate sulfoxide-NHC ligands ( 113 – 118 , Scheme ). These authors also studied the behavior of an analogous thioether-functionalized NHC complex for comparison.…”
Section: Multifunctional N-heterocyclic Carbene Ligandsmentioning
confidence: 99%
“…There are several review articles reported in the past decade, which are dedicated to NHC ligands bearing one additional donor group [ 7 , 8 , 9 , 10 ]. Included in these review articles are bidentate NHC ligands with phosphorous tether [ 11 , 12 , 13 , 14 , 15 , 16 , 17 , 18 , 19 ], nitrogen [ 20 , 21 , 22 , 23 , 24 , 25 , 26 , 27 , 28 , 29 , 30 , 31 , 32 , 33 , 34 , 35 , 36 , 37 ], and oxygen tethers [ 38 , 39 , 40 , 41 , 42 , 43 , 44 , 45 , 46 , 47 , 48 , 49 , 50 , 51 , 52 , 53 , 54 , 55 , 56 , 57 , 58 , 59 ,…”
Section: Introductionmentioning
confidence: 99%